2018
DOI: 10.1080/02656736.2018.1498137
|View full text |Cite
|
Sign up to set email alerts
|

Neoadjuvant chemotherapy plus radiation versus chemotherapy plus regional hyperthermia in high-grade soft tissue sarcomas: a retrospective comparison

Abstract: Purpose: Localized adult high-grade soft tissue sarcomas (STS) usually require multimodality treatment including surgery, radiotherapy, chemotherapy and hyperthermia. If maximal preoperative tumorshrinkage is envisaged, neoadjuvant chemotherapy þ radiation (CRT) is often applied, however at the expense of relatively high toxicities and increased postoperative complication rates. This study aims to compare preoperative CRT with neoadjuvant chemotherapy þ regional hyperthermia (HCT) regarding histopathological r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 48 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Furthermore, there were no significant differences in overall survival (OS), local control, and freedom from distant metastases over 2 years between the 2 groups. 54,55…”
Section: Clinical Use Of Hyperthermiamentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, there were no significant differences in overall survival (OS), local control, and freedom from distant metastases over 2 years between the 2 groups. 54,55…”
Section: Clinical Use Of Hyperthermiamentioning
confidence: 99%
“…Furthermore, there were no significant differences in overall survival (OS), local control, and freedom from distant metastases over 2 years between the 2 groups. 54,55 In a more recent trial, the prospectively randomized NCT 00003052 phase III multicenter trial, 341 patients with untreated localized high-risk STS were enrolled, of whom 169 received neoadjuvant chemotherapy consisting of etoposide, ifosfamide, and adriamycin (EIA) plus regional hyperthermia, and the remainder received EIA alone. After induction therapy, the tumor response was evaluated by imaging, and the best local treatment (surgery and/or RT) was selected, followed by another 4 cycles of induction therapy.…”
Section: Hyperthermia Combined With Chemotherapymentioning
confidence: 99%
“…They could show a significant effect of additional hyperthermia on local PFS, DFS, and OS with an improvement of overall survival and local progression-free survival [22]. A retrospective analysis of the radiooncologic department at the Charité-Universitätsmedizin Berlin also demonstrated a comparable therapeutic response of hyperthermia and radiation therapy in STS in a neoadjuvant setting with a reduced rate of surgical complications in the former group [23]. For that reason, in selected patients we combined doxorubicin/olaratumab with regional hyperthermia in the cohort of patients with borderline resectable localized tumours.…”
Section: 7%mentioning
confidence: 92%
“…One RCT (yielding three publications), [13][14][15] five observational studies [56][57][58][59][60] , and seven single-arm trials [61][62][63][64][65][66][67] were identified. Additionally, one single-arm trial 68 included deep seated sarcomas, and one observational study mixed soft tissue tumours.…”
Section: High-risk Soft-tissue Sarcoma (Sts)mentioning
confidence: 99%